Repeated treatment with high dose cyclophosphamide for severe autoimmune diseases - DeZern, Amy E (e-Century Publishing Corporation, 2013)
High dose cyclophosphamide (HiCY) without stem cell rescue has been shown to induce remissions in patients with severe autoimmune disorders (SADS). However, up to 80% of these patients ultimately relapse. Here we review the outcomes of seven patients treated with two cycles and one patient treated with three cycles of HiCY. The diseases re-treated were scleroderma, multiple sclerosis, three patients with severe aplastic anemia (SAA), and three patients with myasthenia gravis (MG). All but two patients with SAA had received standard immunomodulatory therapy for their disease up front and had been refractory. All patients had complete hematologic recovery. Overall survival in this cohort was 100%. All patients relapsed after the initial cycle but event free survival thereafter was 93.3%. All are still in remission except two MG patients, one of whom relapsed after a severe GI infection requiring hospitalization, and the other relapsed 3 years after the second treatment and she did not respond to the third treatment. This shows that HiCY can be safely re-administered in patients with SAA and refractory SADS. The quality and duration of second remissions appears to be equal or superior to the first remission.